Purpose Fatigue in Modern Organizations and the Declining Credibility of Corporate Value Claims in Stakeholder-Facing Communication - Muthiah Ariqah Mutmainnah Syam (Punggawa Legacy Center, 2026)
Corporate purpose has become a central language of contemporary management, yet its growing visibility does not always strengthen strategic credibility. This study develops the concept of purpose fatigue to explain how corporate value claims can lose persuasive force even when they remain formally acceptable and are not clearly deceptive. Purpose fatigue refers to a gradual decline in credibility that emerges when purpose language becomes intensive, repetitive, semantically similar across firms, and weakly supported by observable organizational action. Using a secondary-data research design, the study proposes a firm-year analysis of annual reports, sustainability reports, chief executive letters, corporate values pages, employee reviews, and business media coverage. Computational content analysis is used to assess purpose intensity, textual repetition, and semantic genericness, while employee sentiment and media tone provide stakeholder-facing indicators of strategic credibility. Purpose-action support is treated as a moderating condition that changes the meaning of value communication. Purpose language may remain credible when attached to traceable decisions, measurable commitments, or reported organizational movement, but the same language may become tiring when stakeholders find little evidence behind repeated claims. The study contributes to management research by moving the debate on corporate purpose beyond the usual opposition between authentic purpose and purpose-washing. It treats purpose as an empirical credibility claim whose strategic value depends on the relationship between communication, action, and stakeholder response.